Antiviral Strategies Using Natural Source-Derived Sulfated Polysaccharides in the Light of the COVID-19 Pandemic and Major Human Pathogenic Viruses - Ray, Bimalendu; Ali, Imran; Jana, Subrata; Mukherjee, Shuvam; Pal, Saikat; Ray, Sayani; Schütz, Martin; Marschall, Manfred (Viruses, 2022)
Only a mere fraction of the huge variety of human pathogenic viruses can be targeted by the currently available spectrum of antiviral drugs. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has highlighted the urgent need for molecules that can be deployed quickly to treat novel, developing or re-emerging viral infections. Sulfated polysaccharides are found on the surfaces of both the susceptible host cells and the majority of human viruses, and thus can play an important role during viral infection. Such polysaccharides widely occurring in natural sources, specifically those converted into sulfated varieties, have already proved to possess a high level and sometimes also broad-spectrum antiviral activity. This antiviral potency can be determined through multifold molecular pathways, which in many cases have low profiles of cytotoxicity. Consequently, several new polysaccharide-derived drugs are currently being investigated in clinical settings. We reviewed the present status of research on sulfated polysaccharide-based antiviral agents, their structural characteristics, structure–activity relationships, and the potential of clinical application. Furthermore, the molecular mechanisms of sulfated polysaccharides involved in viral infection or in antiviral activity, respectively, are discussed, together with a focus on the emerging methodology contributing to polysaccharide-based drug development.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antiviral activities and mechanisms; Antiviral efficacy; Drug structure-activity relationship; Emerging viral infections; Heparin mimetics; In vivo studies; Major human pathogenic viruses; Sulfated polysaccharides; Virus entry as a target

Cyclin‐Dependent Kinases (CDKs) and the Human Cytomegalovirus‐Encoded CDK Ortholog pUL97 Represent Highly Attractive Targets for Synergistic Drug Combinations - Wild, Markus; Hahn, Friedrich; Brückner, Nadine; Schütz, Martin; Wangen, Christina; Wagner, Sabrina; Sommerer, Mona; Strobl, Stefan; Marschall, Manfred (International Journal of Molecular Sciences, 2022)
Human cytomegalovirus (HCMV) is a pathogenic human herpesvirus associated with serious, potentially life‐threatening symptoms in the immunocompromised or immunonaïve host. The limitations encountered by antiviral therapy options currently available include a narrow panel of accessible targets, the induction of viral drug resistance as well as severe drug dosage‐mediated side‐effects. Improved drug‐targeting strategies to resolve these issues are the focus of our investigations. In particular, pharmaceutical kinase inhibitors (PKIs), either directed to host kinases or directed to the viral protein kinase pUL97, have been considered to overcome these restrictions. Recently, we reported the identification of a synergistic combination of two PKIs directed to host cyclin‐dependent kinase 7 (CDK7) and viral CDK ortholog pUL97. Here, we substantiate these findings with the following results: (i) true drug synergy was exhibited by various chemical classes of PKI pairs directed to pUL97 and CDK7; (ii) no putative amplification of cytotoxicity by these drug combinations was observed; (iii) a reduction in drug dosage levels for synergistic combinations was defined on a quantitative basis and compared to monotreatments; (iv) the quantities of target proteins CDK7 and pUL97 expressed in HCMV‐infected cells were assessed by confocal imaging, indicating a strong down‐modulation of CDK7 levels as a result of synergistic drug treatment; (v) the functional importance of these target kinases, both binding to cyclin H, was illustrated by assessing HCMV replication under the viral genomic deletion of ORF‐UL97 or cellular cyclin knock‐out; (vi) new combinations of HCMV‐specific drug synergy were demonstrated for solely host‐directed treatments using PKIs against CDK2, CDK7, CDK8 and/or CDK9 and (vii) a triple PKI combination provided further support for the synergy approach. With these combined findings, this study highlights the potential of therapeutic drug combinations of approved, developmental and preclinical PKIs for expanding future options for anti‐HCMV therapy.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Antiviral drug; Antiviral drug synergism; Cyclin‐dependent kinase (CDK); Direct‐acting antiviral (DAA); Drug combinations; Host‐directed antiviral (HDA); Human cytomegalovirus; New synergistic drug‐target combinations; Pharmaceutical kinase inhibitor (PKI); Viral CDK pUL97 (vCDK)

Cytomegalovirus cyclin-dependent kinase ortholog vCDK/pUL97 undergoes regulatory interaction with human cyclin H and CDK7 to codetermine viral replication efficiency - Schütz, Martin; Wangen, Christina; Sommerer, Mona; Kögler, Melanie; Eickhoff, Jan; Degenhart, Carsten; Klebl, Bert; Naing, Zin; Egilmezer, Ece; Hamilton, Stuart T.; Rawlinson, William D.; Sticht, Heinrich; et al. (Virus Research, 2023)
Human cytomegalovirus (HCMV) infection is shaped by a tightly regulated interplay between viral and cellular proteins. Distinct kinase activities, such as the viral cyclin-dependent kinase ortholog (vCDK) pUL97 and cellular CDK7 are both crucial for efficient viral replication. Previously, we reported that both kinases, vCDK/pUL97 and CDK7, interact with cyclin H, thereby achieving an enhanced level of kinase activity and overall functionality in viral replication. Here we provide a variety of novel results, as generated on a methodologically extended basis, and present a concept for the codetermination of viral replication efficiency through these kinase activities: (i) cyclin H expression, in various human cell types, is substantially upregulated by strains of HCMV including the clinically relevant HCMV Merlin; (ii) vCDK/pUL97 interacts with human cyclin H in both HCMV-infected and plasmid-transfected cell systems; (iii) a doxycycline-inducible shRNA-dependent knock-down (KD) of cyclin H significantly reduces pUL97 activity (qSox in vitro kinase assay); (iv) accordingly, pUL97 in vitro kinase activity is seen significantly increased upon addition of recombinant cyclin H; (v) as a point of specific importance, human CDK7 activity shows an increase by vCDK/pUL97-mediated trans-stimulation (whereas pUL97 is not stimulated by CDK7); (vi) phosphosite-specific antibodies indicate an upregulated CDK7 phosphorylation upon HCMV infection, as mediated through a pUL97-specific modulatory effect (i.e. shown by pUL97 inhibitor treatment or pUL97-deficient viral mutant); (vii) finally, an efficient KD of cyclin H in primary fibroblasts generally results in an impaired HCMV replication efficiency as measured on protein and genomic levels. These results show evidence for the codetermination of viral replication by vCDK/pUL97, cyclin H and CDK7, thus supporting the specific importance of cyclin H as a central regulatory factor, and suggesting novel targeting options for antiviral drugs.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Codetermination of viral replication; Cyclin H knock-down; Functional importance of cyclin H; Human cytomegalovirus; Modulation of vCDK/pUL97 activity in vitro; Options for antiviral drug targeting; pUL97-mediated CDK7 trans-stimulation; vCDK/pUL97–cyclin binding; Viral cyclin-dependent kinase (CDK) ortholog

Exploiting the amazing diversity of natural source-derived polysaccharides: Modern procedures of isolation, engineering, and optimization of antiviral activities - Ray, Bimalendu; Schütz, Martin; Mukherjee, Shuvam; Jana, Subrata; Ray, Sayani; Marschall, Manfred (Polymers, 2021)
Naturally occurring polysaccharide sulfates are highly diverse, owning variations in the backbone structure, linkage pattern and stereochemistry, branching diversity, sulfate content and positions of sulfate group(s). These structural characteristics bring about diverse sulfated polymers with dissimilar negative charge densities and structure–activity relationships. Herein, we start with a short discussion of techniques needed for extraction, purification, chemical sulfation, and structural characterization of polysaccharides. Processes of isolation and sulfation of plant-derived polysaccharides are challenging and usually involve two steps. In this context, we describe an integrated extraction-sulfation procedure that produces polysaccharide sulfates from natural products in one step, thereby generating additional pharmacological activities. Finally, we provide examples of the spectrum of natural source-derived polysaccharides possessing specific features of bioactiv-ity, in particular focusing on current aspects of antiviral drug development and drug–target inter-action. Thus, the review presents a detailed view on chemically engineered polysaccharides, espe-cially sulfated derivatives, and underlines their promising biomedical perspectives.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Amalgamated extraction-sulfation methods; Broad-spectrum bioactivity; Chemical profiles; Natural source-derived compounds; Polysaccharide sulfates; Specific antiviral activities; Structure–activity relationships

Functional Relevance of the Interaction between Human Cyclins and the Cytomegalovirus-Encoded CDK-Like Protein Kinase pUL97 - Schütz, Martin; Steingruber, Mirjam; Socher, Eileen; Müller, Regina; Wagner, Sabrina; Kögel, Merle; Sticht, Heinrich; Marschall, Manfred (Viruses, 2021)
The replication of human cytomegalovirus (HCMV) is characterized by a complex network of virus–host interaction. This involves the regulatory viral protein kinase pUL97, which represents a viral cyclin-dependent kinase ortholog (vCDK) combining typical structural and functional features of host CDKs. Notably, pUL97 interacts with the three human cyclin types T1, H and B1, whereby the binding region of cyclin T1 and the region conferring oligomerization of pUL97 were both assigned to amino acids 231–280. Here, we addressed the question of whether recombinant HCMVs harboring deletions in this region were impaired in cyclin interaction, kinase functionality or viral replication. To this end, recombinant HCMVs were generated by traceless BACmid mutagenesis and were phenotypically characterized using a methodological platform based on qPCR, coimmunoprecipitation, in vitro kinase assay (IVKA), Phos-tag Western blot and confocal imaging analysis. Combined data illustrate the following: (i) infection kinetics of all three recombinant HCMVs, i.e., ORF-UL97 ∆231–255, ∆256–280 and ∆231–280, showed impaired replication efficiency compared to the wild type, amongst which the largest deletion exhibited the most pronounced defect; (ii) specifically, this mutant ∆231–280 showed a loss of interaction with cyclin T1, as demonstrated by CoIP and confocal imaging; (iii) IVKA and Phos-tag analyses revealed strongly affected kinase activity for ∆231–280, with strong impairment of both autophosphorylation and substrate phosphorylation, but less pronounced impairments for ∆231–255 and ∆256–280; and (iv) a bioinformatic assessment of the pUL97–cyclin T1 complex led to the refinement of our current binding model. Thus, the results provide initial evidence for the functional importance of the pUL97–cyclin interaction concerning kinase activity and viral replication fitness.<br
Keywords: human cytomegalovirus; virus-encoded kinase pUL97; viral CDK ortholog; interaction with human cyclin T1; replication-impaired viral mutants; defects in pUL97 activities; pUL97–cyclin functional importance

Highly Conserved Interaction Profiles between Clinically Relevant Mutants of the Cytomegalovirus CDK-like Kinase pUL97 and Human Cyclins: Functional Significance of Cyclin H - Schütz, Martin; Müller, Regina; Socher, Eileen; Wangen, Christina; Full, Florian; Wyler, Emanuel; Wong, Diana D.; Scherer, Myriam; Stamminger, Thomas; Chou, Sunwen; Rawlinson, William D.; Hamilton, Stuart T.; et al. (International Journal of Molecular Sciences, 2022)
The complex host interaction network of human cytomegalovirus (HCMV) involves the regulatory protein kinase pUL97, which represents a viral cyclin-dependent kinase (CDK) ortholog. pUL97 interacts with the three human cyclin types T1, H, and B1, whereby the binding region of cyclin T1 and the pUL97 oligomerization region were both assigned to amino acids 231-280. We further addressed the question of whether HCMVs harboring mutations in ORF-UL97, i.e., short deletions or resistance-conferring point mutations, are affected in the interaction with human cyclins and viral replication. To this end, clinically relevant UL97 drug-resistance-conferring mutants were analyzed by whole-genome sequencing and used for genetic marker transfer experiments. The recombinant HCMVs indicated conservation of pUL97–cyclin interaction, since all viral UL97 point mutants continued to interact with the analyzed cyclin types and exerted wild-type-like replication fitness. In comparison, recombinant HCMVs UL97 Δ231-280 and also the smaler deletion Δ236-275, but not Δ241-270, lost interaction with cyclins T1 and H, showed impaired replication efficiency, and also exhibited reduced kinase activity. Moreover, a cellular knock-out of cyclins B1 or T1 did not alter HCMV replication phenotypes or pUL97 kinase activity, possibly indicating alternative, compensatory pUL97–cyclin interactions. In contrast, however, cyclin H knock-out, similar to virus deletion mutants in the pUL97–cyclin H binding region, exhibited strong defective phenotypes of HCMV replication, as supported by reduced pUL97 kinase activity in a cyclin H-dependent coexpression setting. Thus, cyclin H proved to be a very relevant determinant of pUL97 kinase activity and viral replication efficiency. As a conclusion, the results provide evidence for the functional importance of pUL97–cyclin interaction. High selective pressure on the formation of pUL97–cyclin complexes was identified by the use of clinically relevant mutants<br

Human Cytomegalovirus Dysregulates Cellular Dual-Specificity Tyrosine Phosphorylation-Regulated Kinases and Sonic Hedgehog Pathway Proteins in Neural Astrocyte and Placental Models - Egilmezer, Ece; Hamilton, Stuart T.; Lauw, Glen; Follett, Jasmine; Sonntag, Eric; Schütz, Martin; Marschall, Manfred; Rawlinson, William D. (Viruses, 2024)
Human cytomegalovirus (CMV) infection is the leading non-genetic cause of congenital malformation in developed countries, causing significant fetal injury, and in some cases fetal death. The pathogenetic mechanisms through which this host-specific virus infects then damages both the placenta and the fetal brain are currently ill-defined. We investigated the CMV modulation of key signaling pathway proteins for these organs including dual-specificity tyrosine phosphorylation-regulated kinases (DYRK) and Sonic Hedgehog (SHH) pathway proteins using human first trimester placental trophoblast (TEV-1) cells, primary human astrocyte (NHA) brain cells, and CMV-infected human placental tissue. Immunofluorescence demonstrated the accumulation and re-localization of SHH proteins in CMV-infected TEV-1 cells with Gli2, Ulk3, and Shh re-localizing to the CMV cytoplasmic virion assembly complex (VAC). In CMV-infected NHA cells, DYRK1A re-localized to the VAC and DYRK1B re-localized to the CMV nuclear replication compartments, and the SHH proteins re-localized with a similar pattern as was observed in TEV-1 cells. Western blot analysis in CMV-infected TEV-1 cells showed the upregulated expression of Rb, Ulk3, and Shh, but not Gli2. In CMV-infected NHA cells, there was an upregulation of DYRK1A, DYRK1B, Gli2, Rb, Ulk3, and Shh. These in vitro monoculture findings are consistent with patterns of protein upregulation and re-localization observed in naturally infected placental tissue and CMV-infected ex vivo placental explant histocultures. This study reveals CMV-induced changes in proteins critical for fetal development, and identifies new potential targets for CMV therapeutic development.
CRIS-Team Scopus Importer:2024-07-12
Keywords: astrocytes; cytomegalovirus; developmental pathways; pathogenesis; placenta

Recombinant Human Cytomegalovirus Expressing an Analog-Sensitive Kinase pUL97 as Novel Tool for Functional Analyses - Krämer, Nadine; Schütz, Martin; Mato, Uxía Gestal; Herhaus, Lina; Marschall, Manfred; Zimmermann, Christine (Viruses, 2022)
The human cytomegalovirus (HCMV) is a member of the beta-herpesvirus family and inflicts life-long latent infections in its hosts. HCMV has been shown to manipulate and dysregulate many cellular processes. One major interactor with the cellular host is the viral kinase pUL97. The UL97 gene is essential for viral replication, and kinase-deficient mutants of pUL97 display a severe replication defect. Recently, another group established an analog-sensitive version of the pUL97 protein. This mutant kinase can be treated with a non-hydrolysable ATP analog, thereby inhibiting its kinase function. This process is reversible by removing the ATP analog by media change. We introduced this mutant version of the pUL97 protein into the laboratory strain Ad169 of HCMV, BADwt, creating a BAD-UL97-as1 viral mutant. This mutant virus replicated normally in infected cells in the absence of the ATP analog and maintained its ability to phosphorylate its cellular substrates. However, when treated with the ATP analog, BAD-UL97-as1 displayed a defect in the production of intra- and extracellular viral DNA and in the production of viral progeny. Furthermore, in the presence of 3MB-PP1, a well-established substrate of pUL97 was no longer hyperphosphorylated. This effect was detectable as early as 4 h post treatment, which allows for studies on pUL97 without the complication of low viral titers. Nevertheless, we observed off-target effects of 3MB-PP1 on several cellular processes, which should be considered with this approach.
CRIS-Team Scopus Importer:2022-11-04
Keywords: analog-sensitive pUL97 variant; BACmid-derived recombinant HCMV; functional analyses; human cytomegalovirus (HCMV); protein kinase pUL97; pUL97-specific inhibitors; viral kinase activity

'Shared-Hook' and 'Changed-Hook' Binding Activities of Herpesviral Core Nuclear Egress Complexes Identified by Random Mutagenesis - Lösing, Josephine; Haege, Sigrun; Schütz, Martin; Wagner, Sabrina; Wardin, Julia; Sticht, Heinrich; Marschall, Manfred (Cells, 2022)
Herpesviruses replicate their genomes and assemble their capsids in the host cell nucleus. To progress towards morphogenesis in the cytoplasm, herpesviruses evolved the strategy of nuclear egress as a highly regulated process of nucleo-cytoplasmic capsid transition. The process is conserved among alpha-, beta- and gamma-herpesviruses and involves the formation of a core and multicomponent nuclear egress complex (NEC). Core NEC is assembled by the interaction between the nucleoplasmic hook protein, i.e., pUL53 (human cytomegalovirus, HCMV), and the integral membrane-associated groove protein, i.e., pUL50. Our study aimed at the question of whether a panherpesviral NEC scaffold may enable hook-into-groove interaction across herpesviral subfamilies. For this purpose, NEC constructs were generated for members of all three subfamilies and analyzed for multi-ligand interaction using a yeast two-hybrid (Y2H) approach with randomized pUL53 mutagenesis libraries. The screening identified ten library clones displaying cross-viral shared hook-into-groove interaction. Interestingly, a slightly modified Y2H screening strategy provided thirteen further changed-hook pUL53 clones having lost parental pUL50 interaction but gained homolog interaction. In addition, we designed a sequence-predicted hybrid construct based on HCMV and Epstein-Barr virus (EBV) core NEC proteins and identified a cross-viral interaction phenotype. Confirmation was provided by applying protein-protein interaction analyses in human cells, such as coimmunoprecipitation settings, confocal nuclear rim colocalization assays, and HCMV Delta UL53 infection experiments with pUL53-complementing cells. Combined, the study provided the first examples of cross-viral NEC interaction patterns and revealed a higher yield of human cell-confirmed binding clones using a library exchange rate of 3.4 than 2.7. Thus, the study provides improved insights into herpesviral NEC protein binding specificities of core NEC formation. This novel information might be exploited to gain a potential target scaffold for the development of broadly acting NEC-directed inhibitory small molecules.
CRIS-Team WoS Importer:2023-01-27

The Artemisinin-Derived Autofluorescent Compound BG95 Exerts Strong Anticytomegaloviral Activity Based on a Mitochondrial Targeting Mechanism - Wild, Markus; Hahn, Friedrich; Grau, Benedikt; Herrmann, Lars; Niesar, Aischa; Schütz, Martin; Lorion, Melanie M.; Ackermann, Lutz; Tsogoeva, Svetlana; Marschall, Manfred (International Journal of Molecular Sciences, 2020)
Human cytomegalovirus (HCMV) is a major human pathogen associated with severe pathology. Current options of antiviral therapy only partly satisfy the needs of a well-tolerated long-term treatment/prophylaxis free from drug-induced viral resistance. Recently, we reported the strong antiviral properties in vitro and in vivo of the broad-spectrum anti-infective drug artesunate and its optimized derivatives. NF-κB signaling was described as a targeting mechanism and additional target proteins have recently been identified. Here, we analyzed the autofluorescent hybrid compound BG95, which could be utilized for intracellular visualization by confocal imaging and a tracking analysis in virus-infected primary human fibroblasts. As an important finding, BG95 accumulated in mitochondria visualized by anti-prohibitin and MitoTracker staining, and induced statistically significant changes of mitochondrial morphology, distinct from those induced by HCMV infection. Notably, mitochondrial membrane potential was found substantially reduced by BG95, an effect apparently counteracting efficient HCMV replication, which requires active mitochondria and upregulated energy levels. This finding was consistent with binding properties of artesunate-like compounds to mitochondrial proteins and thereby suggested a new mechanistic aspect. Combined, the present study underlines an important role of mitochondria in the multifaceted, host-directed antiviral mechanism of this drug class, postulating a new mitochondria-specific mode of protein targeting.
CRIS-Team Scopus Importer:2020-08-14
Keywords: antiviral drugs; artemisinin derivative; autofluorescence; human cytomegalovirus; intracellular tracking; mitochondrial architecture; mitochondrial impairment; mitochondrial targeting

The Interactive Complex between Cytomegalovirus Kinase vCDK/pUL97 and Host Factors CDK7-Cyclin H Determines Individual Patterns of Transcription in Infected Cells. - Schütz, Martin; Cordsmeier, Arne; Wangen, Christina; Horn, Anselm; Wyler, Emanuel; Enßer, Armin; Sticht, Heinrich; Marschall, Manfred (International Journal of Molecular Sciences, 2023)
The infection of human cytomegalovirus (HCMV) is strongly determined by the host-cell interaction in a way that the efficiency of HCMV lytic replication is dependent on the regulatory interplay between viral and cellular proteins. In particular, the activities of protein kinases, such as cyclin-dependent kinases (CDKs) and the viral CDK ortholog (vCDK/pUL97), play an important role in both viral reproduction and virus-host interaction. Very recently, we reported on the complexes formed between vCDK/pUL97, human cyclin H, and CDK7. Major hallmarks of this interplay are the interaction between cyclin H and vCDK/pUL97, which is consistently detectable across various conditions and host cell types of infection, the decrease or increase in pUL97 kinase activity resulting from cyclin H knock-down or elevated levels, respectively, and significant trans-stimulation of human CDK7 activity by pUL97 in vitro. Due to the fact that even a ternary complex of vCDK/pUL97-cyclin H-CDK7 can be detected by coimmunoprecipitation and visualized by bioinformatic structural modeling, we postulated a putative impact of the respective kinase activities on the patterns of transcription in HCMV-infected cells. Here, we undertook a first vCDK/pUL97-specific transcriptomic analysis, which combined conditions of fully lytic HCMV replication with those under specific vCDK/pUL97 or CDK7 drug-mediated inhibition or transient cyclin H knockout. The novel results were further strengthened using bioinformatic modeling of the involved multi-protein complexes. Our data underline the importance of these kinase activities for the C-terminal domain (CTD) phosphorylation-driven activation of host RNA polymerase in HCMV-infected cells. The impact of the individual experimental conditions on differentially expressed gene profiles is described in detail and discussed.
EVALuna2:545510

The peptidyl-prolyl cis/trans isomerase Pin1 interacts with three early regulatory proteins of human cytomegalovirus - Schütz, Martin; Thomas, Marco; Wangen, Christina; Wagner, Sabrina; Rauschert, Luisa; Errerd, Theresa; Kießling, Melissa; Sticht, Heinrich; Milbradt, Jens; Marschall, Manfred (Virus Research, 2020)
Human cytomegalovirus (HCMV) is a ubiquitous human pathogen of high clinical relevance. Despite intensive research of virus-host interaction, crucial details still remain unknown. In this study, the role of the cellular peptidyl-prolyl cis/trans isomerase Pin1 during HCMV infection was investigated. Pin1 is able to recognize phosphorylated serine/threonine-proline motifs and regulates the structural conformation, stability and function of its substrates. Concerning HCMV replication, our recent studies revealed that Pin1 plays an important role in viral nuclear egress by contributing to the depletion of the nuclear lamina at distinct sites through the cis/trans conversion of lamin proteins. Here, novel data illustrate the HCMV-induced upregulation of Pin1 including various cell types being permissive, semi-permissive or non-permissive for productive HCMV replication. Addressing the question of functional impact, Pin1 knock-out (KO) did not show a measurable effect on viral protein expression, at least when assessed by Western blot analysis. Applying highly sensitive methods of qPCR and plaque titration, a pharmacological inhibition of Pin1 activity, however, led to a significant decrease of viral genome equivalents and production of infectious virus, respectively. When focusing on the identification of viral proteins interacting with Pin1 by various coimmunoprecipitation (CoIP) settings, we obtained positive signals for (i) the core nuclear egress complex protein pUL50, (ii) the viral mRNA export factor pUL69 and (iii) the viral DNA polymerase processivity factor pUL44. Confocal immunofluorescence analysis focusing on partial colocalization between Pin1 and the coexpressed viral proteins pUL50, pUL69 or pUL44, respectively, was consistent with the CoIP experiments. Mapping experiments, using transient expression constructs for a series of truncated protein versions and specific replacement mutants, revealed a complex pattern of Pin1 interaction with these three early regulatory HCMV proteins. Data suggest a combination of different modes of Pin1 interactions, involving both classical phosphorylation-dependent Pin1 binding motifs and additional phosphorylation-independent binding sites. Combined, these results support the concept that Pin1 may play an important role in several stages of HCMV infection, thus determining viral replicative efficiency.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cytomegalovirus replication; Phosphorylation-independent interaction; Pin1 inhibitor-mediated viral replication block; Pin1 interaction with pUL50; Pin1 upregulation; Prolyl cis/trans isomerase Pin1; pUL44; pUL69

Understanding the Cytomegalovirus Cyclin-Dependent Kinase Ortholog pUL97 as a Multifaceted Regulator and an Antiviral Drug Target - Marschall, Manfred; Schütz, Martin; Wild, Markus; Socher, Eileen; Wangen, Christina; Dhotre, Kishore; Rawlinson, William D.; Sticht, Heinrich (Cells, 2024)
Herpesviral protein kinases, such as the therapy-relevant pUL97 of human cytomegalovirus (HCMV), are important for viral replication efficiency as well as pathogenesis, and represent key antiviral drug targets. HCMV pUL97 is a viral cyclin-dependent kinase (CDK) ortholog, as it shares functional and structural properties with human CDKs. Recently, the formation of vCDK/pUL97–cyclin complexes and the phosphorylation of a variety of viral and cellular substrate proteins has been demonstrated. Genetic mapping and structural modeling approaches helped to define two pUL97 interfaces, IF1 and IF2, responsible for cyclin binding. In particular, the regulatory importance of interactions between vCDK/pUL97 and host cyclins as well as CDKs has been highlighted, both as determinants of virus replication and as a novel drug-targeting option. This aspect was substantiated by the finding that virus replication was impaired upon cyclin type H knock-down, and that such host-directed interference also affected viruses resistant to existing therapies. Beyond the formation of binary interactive complexes, a ternary pUL97–cyclin H–CDK7 complex has also been described, and in light of this, an experimental trans-stimulation of CDK7 activity by pUL97 appeared crucial for virus–host coregulation. In accordance with this understanding, several novel antiviral targeting options have emerged. These include kinase inhibitors directed to pUL97, to host CDKs, and to the pUL97–cyclin H interactive complexes. Importantly, a statistically significant drug synergy has recently been reported for antiviral treatment schemes using combinations of pharmacologically relevant CDK7 and vCDK/pUL97 inhibitors, including maribavir. Combined, such findings provide increased options for anti-HCMV control. This review focuses on regulatory interactions of vCDK/pUL97 with the host cyclin–CDK apparatus, and it addresses the functional relevance of these key effector complexes for viral replication and pathogenesis. On this basis, novel strategies of antiviral drug targeting are defined.<br
Keywords: herpesviral protein kinases; human cytomegalovirus; cytomegaloviral vCDK/pUL97; regulation of viral replication; impact of vCDK/pUL97; cyclin H and CDK7; antiviral approaches with kinase inhibitors; novel targeting strategies